Normative translation in the heterogeneity of law. (2nd October 2015) - Hasegawa, Ko
Abstract : In the diffusion of law, there are many connecting points between different legal systems and one of them is the translational process between divergent legal ideas. In many parts of the world, the translation of foreign legal ideas into domestic language has been the starting point of the reception of law and also one of the continuous inputs for the development of law. Arguing that it is important to investigate the features of normative translation in order to understand the normative dynamics in the diffusion of law, this article explores those features from the perspective of hermeneutics that emphasises the interpretive nature of our intellectual activities and also of legal philosophy that focuses on the structure of our legal thinking. In so doing, this article also points out some significant aspects for the deeper understanding of the cultural complexity in the diffusion of law.